Sociology of Education - Theories, Communities, Contexts - Zsófia Vincze (Debrecen University Press, 2023)
Bibliography of the reviewed book: Pusztai, G. (Eds.), (2023). Sociology of Education - Theories, communities, contexts. Debrecen University Press.